Pengembangan Keterampilan Pemuda Melalui Pelatihan Public Speaking dan Desain Grafis di Desa Ekowisata Pancoh - Bayu, Andhika Bayu; Damastuti, Riski; Kiki Astria, Kadek (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
This community service program aims to enhance the capacity of Karang Taruna youth in Pancoh Ecotourism Village in public speaking and graphic design as a strategy to promote local tourism potential. The main issues identified were the lack of communication and digital design skills, which hindered the village’s visibility in the digital sphere. The training was conducted through a participatory approach involving interactive presentations and hands-on practice using Canva. The results showed a significant improvement in participants’ confidence in public speaking and their ability to create informative and visually appealing promotional materials. Beyond providing technical skills, the program fostered active youth involvement in sustainable ecotourism development. In the long term, the training is expected to lay a foundation for building adaptive human resources and creative village teams capable of implementing digital promotion strategies. Further training and continuous mentoring are recommended to maximize the impact on village tourism development.